«Apocryphal Nightmares». Observations on the Reference to Damascius in The Nameless City by Howard Phillips Lovecraft - Napoli, Valerio (Peitho. Examina Antiqua, 2014)
In his tale entitled The Nameless City, Howard Phillips Lovecraft includes unspecified «paragraphs from the apocryphal nightmares of Damascius» among the «fragments» of the «cherished treasury of daemoniac lore» of the protagonist In the present essay, I suggest that there is a connection between this unusual reference and a note in the writer’s Commonplace Book, which refers to the notice by Photius (Bibl. cod. 130) on a lost work by Damascius that nowdays is generally referred to as Paradoxa and assumed to consist of a variegated collection of extraordinary stories and facts. I, therefore, delineate a general presentation of the testimony by the Byzantine Patriarch (very probably only indirectly known to Lovecraft), upon which I attempt to bring into focus the motivations that led the Providence to make the writer insert the name of Damascius in the fantastic plot of his story.